Isitya esihle (asidleli) - Nqaba, Nobukho (Michaelis School of Fine Art, 2025)
This fine art project looks at my life story through exploring memories of growing up in Grabouw, a rural apple farming community outside of Cape Town. This community is marginalized due to socio-economic circumstances as a legacy of apartheid. I argue that autobiography has mostly been associated with written text, but the memoir and story of someone's life can also be told visually using visual imagery. I take the stance that autobiography is a tool in which my story - and that of my parents and community – connect and do this by drawing on objects and materials that are specific to my memories of growing up in the area. I unpack my life story through the family photo album. I elaborate on the absence of family photographs and how this has enabled me to find imaginative ways of retelling my past. I expand on how the community has mostly been represented, through journalistic reports, often presenting people in vulnerable and tragic positions. I state that my desire is for the community not to be presented in such ways, as it further perpetuates negative stereotypes about workers, and takes away their agency. I write about my mother who was a farm worker, her friend, and some of our neighbours who still live in the area and retell parts of their stories in imaginative and performative ways in the photographic studio, mining memories of my childhood. I describe some aspects of the artwork, such as photographs, installation, video, and books, elaborating on the narrative and themes behind them and their significance to me and the people involved in the project. I use the blue workers overalls prominently throughout the project, which are worn on the farm and are a marker of a person's social class. The overall aim of this project is to represent the community in a way that dignifies them. I am using art as an expressive tool to talk about pertinent issues. I aim, through this artwork, to bring awareness about the lived experiences of the Grabouw community, to shift mindsets about how the farming community and marginalized people are seen in broader society. This document is presented from a story-telling perspective and often incorporates everyday isiXhosa words to connect the project to a personal experience.